2009
DOI: 10.1007/s11214-008-9471-8
|View full text |Cite
|
Sign up to set email alerts
|

Electric Fields and Magnetic Fields in the Plasmasphere: A Perspective From CLUSTER and IMAGE

Abstract: The electric field and magnetic field are basic quantities in the plasmasphere measured since the 1960s. In this review, we first recall conventional wisdom and remaining problems from ground-based whistler measurements. Then we show scientific results from CLUSTER and IMAGE, which are specifically made possible by newly introduced features on these spacecraft, as follows. 1. In situ electric field measurements using artificial elec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 109 publications
(139 reference statements)
1
4
0
Order By: Relevance
“…In addition, there is an eastward drift channel in the midnight-morning sector, which is also consistent with the statistical patterns of SAPS [Foster and Vo, 2002]. Same SAPS fields are applied in both the northern and southern hemispheres as observations have shown that there is almost perfect mapping of SAPS electric field between the conjugate hemispheres [Anderson et al, 2001;Puhl-Quinn et al, 2007;Mishin and Puhl-Quinn, 2007;Matsui et al, 2009].…”
Section: The Saps-tiegcmsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, there is an eastward drift channel in the midnight-morning sector, which is also consistent with the statistical patterns of SAPS [Foster and Vo, 2002]. Same SAPS fields are applied in both the northern and southern hemispheres as observations have shown that there is almost perfect mapping of SAPS electric field between the conjugate hemispheres [Anderson et al, 2001;Puhl-Quinn et al, 2007;Mishin and Puhl-Quinn, 2007;Matsui et al, 2009].…”
Section: The Saps-tiegcmsupporting
confidence: 76%
“…They are found to be confined in a latitudinally very narrow (∼1°–2°) region and coincide with the ionospheric footprint of the plasmapause [ Smidy et al , 1977; Anderson et al , 2001] and the location of the middle latitude ionospheric F region plasma density trough [ Anderson et al , 1991]. Later, Yeh et al [1991] and Foster and Vo [2002] used observations by the Millstone incoherent scattering radar to show that subauroral sunward plasma drifts can occur over a wider latitude region and often contain narrower and more intense PJ/SAIDs during geomagnetically active periods [ Matsui et al , 2009, and references therein]. Foster and Burke [2002] then proposed to use the term Subauroral Polarization Stream (SAPS) to include all observations of subauroral plasma flows and electric fields equatorward of the regular high latitude evening convection cell and diffuse aurora [ Oksavik et al , 2006; Baker et al , 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Figure exemplifies meridional electric fields in the dipole meridian system (DMS) from (Figure a) C1 and DMSP F16 on 8 April 2004 and (Figure b) C1, DMSP F14, and Polar on 18 March 2002 [cf. PQ07, Figure and Matsui et al , , Figure ]. Here + Y dms points eastward, + Z dms is along magnetic north, and X dms − Z dms is the meridional plane at ≈21:50 MLT (8 April 2004) and at 23:00 MLT (18 March 2002).…”
Section: Near‒equatorial Substorm Said Eventsmentioning
confidence: 93%
“…The related electric field causes an erosion of the plasmasphere in the dusk sector driving sunward flowing plumes, and contributes to the dynamics of the PP (Goldstein et al, 2005;Brandt et al, 2005). These events are accompanied by Sub-Auroral Polarisation Streams (SAPS) (Goldstein et al, 2005;Matsui et al, 2009) at ionospheric altitudes.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%